Implementation of Extemporaneous Preparation Using Bar Coding Technology - Bahmaid, Najla Abdulbari (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2017)
Extemporaneous Preparation (Drug Compounding) - the creation of a drug product by mixing ingredients - is an important part of ensuring that medications are available to meet individual patient needs, the quality and extent of drug compounding have surfaced as important issues in recent years. For example, several compounding cases in the last several years have resulted in critical diseases and deaths, raising concern about observation to ensure the safety of compounded drugs. This paper lays the groundwork for the development of Extemporaneous Preparation system. This system facilitates compounding process in systemic approach in the pharmacy of king Faisal Specialist Hospital and Research Centre -non profit tertiary care hospital- to prevent manual errors and improve patient safety and quality by using bar coding technology.